INVESTIGATION OF MIR-BART 13 AND 15 IN PATIENTS WITH ALLERGOPATHY IN COMBINATION WITH CHRONIC EPSTEIN-BARR VIRAL INFECTION - Zubchenko, S.O.; Chopyak, V.V.; Havrylyuk, A.M.; Potemkina, G.O.; Lomikovska, M.P. (World of Medicine and Biology, 2019)
Epstein-Barr (EBV) virus initiates a wide spectrum of immunomodulating effects in the human body. EBV is one of the first viruses, in which expression of miRNAs has been revealed, that are used as targets for detection of the virus in clinical investigations. To investigate association relationships of miR-BART 13 and 15 in patients with allergopathy and chronic EBV-infection in active and latent phases. In general, 46 patients with chronic EBV-infection in active/latent phases have been examined, age 18-59 years, 65% of females, 37% of males. Clinical, general laboratory, instrumental, specific allergological, molecular genetic, and cytological investigations were performed. High levels of miR-BART 13 expression were detected in patients with allergopathy in combination with chronic EBV-infection in active (р